Czego warto się uczyć w zakresie zarządzania od Dalekiego Wschodu? - Karczewski, Leszek (Człowiek i Społeczeństwo, 2018)
Leszek Karczewski, Czego warto się uczyć w zakresie zarządzania od Dalekiego Wschodu? [What is worth to learn in management from the Far East?] edited by W. Banach, M.A. Michalski, J. Sójka, „Człowiek i Społeczeństwo” vol. XLVI: Między Chinami a Zachodem. Pytanie o źródła chińskiego sukcesu gospodarczego [Between China and the West. An inquiry into the sources of the Chinese economic miracle], Poznań 2018, pp. 159–174, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271. The article emphasizes the need of learning from one’s own history mistakes and the success of other countries such as Japan and China. The author presented the current situation of Poland in both skeptical and optimistic perspectives. The transformation of 1989 is indicated as the genesis of current challenges of the country. In the next part of the article there are suggested actions that could be taken after the transformation in the field of state and organization management in order to realize the idea of Poland as the “second Japan”. The last part of the article is devoted to describing what can still be learned from the Far East countries in the field of economy and management.